Analysis Of Accounting Information Systems In The Atm Transaction Process At Bank Sumsel Babel Kcp Pasar Atas Lubuklinggau - Raynaldo Saputra Simatupang; Yun Fitriano; Ida Ayu Made ER Meytha Gayatri (Penerbit Jurnal Indonesia, 2023)
The aim of this research is to compare whether the accounting information system in the ATM withdrawal process at Bank Sumsel Babel KCP Pasar Atas Lubuklinggau with the accounting information system theory put forward by DeLone and McLean is appropriate/not appropriate. The analytical method used is descriptive with a qualitative approach. This research was conducted at Bank Sumsel Babel KCP Pasar Atas Lubuklinggau in September 2023 – January 2024.The results of the research show that the transaction accounting information system on ATM machines is supported by an information system that uses sophisticated technology in accordance with the theory of accounting information systems put forward by DeLone and McLean both in terms of adaptation, system reliability, response time and usability.